Karakteristik Krim Kunyit Daun Asam (Curcuma domestica Val. - Tamarindus indica L.) pada Perlakuan Konsentrasi Emulsifier dan Waktu Pengadukan - ., Mujahidah; Mulyani, Sri; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This study aimed to know cream of turmeric tamarind leaves on the treatment of concentration emulsifier and stirring time and to determine the concentration emulsifier and stirring time to produce characteristics of cream fulfill requirement of SNI. This study used a randomized block design with two factors. The first factor was the concentration emulsifier which consist of three levels, namely 3, 5 and 7%. The second factor is stirring time which consist of three levels, namely 5, 7.5 and 10 minutes. The data were analyzed by analysis of variance (ANOVA) and continued with the tukey test. The result of the study showed that concentration emulsifier has an effect on the adhesion time, pH, viscocity and spread power. The stirring time has an effect on the adhesion time. Concentration emulsifier 5% and 7% with stirring time 10 minutes were creams that fulfill requirement of SNI. The characteristics cream of concentration emulsifier 5% with stirring time 10 minutes is: homogeneus, separation ratio = 1, adhetion time 48.52 seconds, viscocity 3550 cp, spread power 6.72 cm and pH 6.60. The characteristics cream of concentration emulsifier 7% with stirring time 10 minutes is: homogeneus, separation ratio = 1, adhetion time 28.82 seconds, viscocity 3650 cp, spread power 6.79 cm and pH 6.45. Keywords : Span 80, tween 80, stirring time, turmeric and tamarind leaves.